2018
DOI: 10.1371/journal.pone.0195464
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to medical therapy by serum soluble (pro)renin receptor levels in Graves’ disease

Abstract: Antithyroid drugs are generally selected as the first-line treatment for Graves’ Disease (GD); however, the existence of patients showing resistance or severe side effects to these drugs is an important issue to be solved. The (pro)renin receptor [(P)RR] is a multi-functional protein that activates the tissue renin-angiotensin system and is an essential constituent of vacuolar H+-ATPase, necessary for the autophagy-lysosome pathway. (P)RR is cleaved to soluble (s)(P)RR, which reflects the status of (P)RR expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nevertheless, higher ATP6AP2 expression was associated with greater IgA deposits and more severe phenotypes . Additionally, in Graves' disease, a thyroid‐specific autoimmune disease, ATP6AP2 has been reported to be a potential disease and therapeutic biomarker …”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, higher ATP6AP2 expression was associated with greater IgA deposits and more severe phenotypes . Additionally, in Graves' disease, a thyroid‐specific autoimmune disease, ATP6AP2 has been reported to be a potential disease and therapeutic biomarker …”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 99%
“…187 Additionally, in Graves' disease, a thyroid-specific autoimmune disease, ATP6AP2 has been reported to be a potential disease and therapeutic biomarker. 188…”
Section: Atp6ap2-cdgmentioning
confidence: 99%
“…It has been shown that basal blood s(P)RR levels differ among reports with a tendency of blood s(P)RR levels to be high in older subjects [4,20], patients with heart failure [7], renal dysfunction [21], or Graves' disease [22], and pregnant women [23,24]. The reason of the alterations of these values may be due to the differences of the disease and conditions of the subjects [24].…”
Section: Serum S(p)rr Levelsmentioning
confidence: 99%
“…The mechanisms behind resistance to ATS are poorly understood [8] [9]. The MDR-1 multidrug resistance gene, which is responsible for resistance to a wide variety of drugs in human cells, is potentially involved [10].…”
Section: Commentsmentioning
confidence: 99%
“…Recent studies demonstrated that low baseline thyroglobulin autoantibodies are associated with refractoriness of Graves' disease to ATD treatment [8] [9]. Therefore, they could serve as biomarkers to predict the failure of ATD treatment in such patients.…”
Section: Commentsmentioning
confidence: 99%